Preschool teachers’ beliefs and classroom practices of child-centred learning at private preschools in central region, Malaysia - Wai Leng, Anna Phang; Hui-Shen, Carynne Loh; Dhamotharan, Mogana; Che Mustafa, Mazlina (Southeast Asia Early Childhood Journal, 2021)
Preschool education is an essential early learning experience in the world of education. It has been recognized as the most critical period in child development as quality preschool education makes significant contribution for the development of the whole child. Malaysia preschool education is always emphasizing on the holistic approach with developmentally appropriate preschool programme. The mission is to bring about a paradigm shift from ‘teacher-centred’ to “child- centred’ education to promote active learning in the 21st century classroom. Classroom practices are the educational process for effective teaching and learning. It is the fundamental to young children’s learning. Therefore, teachers’ beliefs and practices are crucial for improving the educational processes. The objectives of this study are to explore the preschool teachers’ beliefs and classroom practices for child-centred learning in preschool education, as well as to investigate the relationship between teachers’ practices and beliefs. This study adopted the quantitative approach. Descriptive statistics and Pearson correlational analysis were used to analyse the data collected. The participants involved 580 preschool teachers of the private sectors in Selangor and Kuala Lumpur areas. A questionnaire of 52-item was used. This tool was administered to measure preschool teachers’ beliefs and classroom practices. In conclusion, the result reported that teachers’ beliefs and classroom practices showed high degree of practices. However, the findings revealed that the reciprocal relationship with parents needs to be enhanced. Further findings indicated that there is strong relationship between teachers’ beliefs and classroom practices.